Pattern of bacterial infection in acute exacerbation of bronchiectasis according to the lobar distribution - Chandra Paul, Shipan; Sarkar, Gopal Chandra; Kumar Paul, Susanta; Chakrabortty, Rajashish; Ahmed, Shamim; Rahman , Mohammed Atiqur (International Journal of Research in Medical Sciences, 2023)
Background: The pattern of bacterial infection in acute exacerbation of bronchiectasis is varied with geographical area and lobar distribution of bronchiectasis. The exact pattern of bacterial infection in acute exacerbation of bronchiectasis according to lobar distribution is not known in our country. This study aimed to investigate the pattern of bacterial infection in acute exacerbation of bronchiectasis according to lobar distribution. Methods: A total of eighty-four patients diagnosed with acute exacerbation of bronchiectasis were included in this cross-sectional study in the department of respiratory medicine, Bangabandhu Sheikh Mujib Medical University. Sputum culture and real-time polymerase chain reaction were used to characterize the bacterial profile and high-resolution computed tomography scans for the location of the bronchiectasis. Before enrolment, informed written consent was obtained from the participants. Results: The mean (SD) age of this study population was 47.89 (±14.95) years, 29.8% were female and 60.7% were a non-smoker. Bronchiectasis was more common in the right middle lobe (63.1%), followed by the right lower lobe (44%), and the left lower lobe (42%). Bacteria were isolated in 66% of patients and Gram-negative bacteria were predominant (78.6%). Pseudomonas aeruginosa (25%) and Klebsiella pneumoniae (17.9%) were the most common bacteria. Conclusions: Pseudomonas aeruginosa was identified predominantly in the right upper lobe, right middle lobe, left upper lobe, and bilateral upper lobe and Klebsiella pneumoniae was in the right lower lobe, left lower lobe, and bilateral lower lobe.